Abnormal Comparison Analysis of Return and Trading Volume Activity Before and After The Announcement of The Covid 19 Pandemic - Marsuni, Nur Sandi; Arum, Ruki Ambar; Mariana, Lina; Nersiyanti, Nersiyanti (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
The Covid-19 pandemic has been a significant turning point in global history, not only from a public health perspective but also in the context of its impact on economic stability, including capital markets. This research aims to analyze the reaction of the Indonesian capital market to the first case of Covid-19 by focusing on two indicators, namely Abnormal Return (AR) and Trading Volume Activity (TVA). Observations were carried out seven days before and seven days after the first announcement of Covid-19 in Indonesia. The research population includes Financial sector companies listed in February and March 2020 on the Indonesia Stock Exchange (BEI). The purposive sampling method was used to select 30 financial companies that met certain criteria. A quantitative approach and comparative method were used in this research, tested using the Wilcoxon Signes Rank Test. The research results show significant differences in AR before and after the announcement of the Covid-19 pandemic. The increase in Abnormal Returns after the announcement indicates that investors tend to trust companies that already have a record of returns or profits before the event, rather than having to rely on predictions of future profits. The Wilcoxon Signed Rank Test results also revealed significant differences in Trading Volume Activity before and after the Covid announcement, indicating changes in trading activity in the capital market. This research provides insight into how the Indonesian capital market responds to health crisis events such as Covid-19, and can serve as a basis for further understanding of economic and financial dynamics in facing similar challenges.